Replication Data for: Soil Biological Indices in Short and Long-Term Experiments in Kenya - Bolo, Peter Omondi; Ayuke, Fredrick O.; Kinyua, Michael; Kihara, Job Maguta (International Center for Tropical Agriculture, 2019)
Improving soil health by utilizing the appropriate tillage, cropping systems and soil management practices is important for enhanced soil quality and agricultural productivity. Of key importance is effect of these factors on the persistence of soil faunal diversity, biomass and their performance in the soil. Studies on the interactive effects of tillage, cropping systems and management practices on soil biology, diversity, abundance and activities in tropical agriculture is still scanty. With that regard, this study was crucial in investigating the effects of different tillage and cropping systems with varying rates of organic and inorganic inputs (i.e., maize stubble, manure, inorganic fertilizers and lime) on the abundance, biomass, taxonomic diversity and extracellular phosphatase enzyme activities of soil microbes, macro and mesofauna. Both Conservation agriculture and conventional tillage with rotations, intercrops and continuous cereal and legumes were compared within two long-term experiments, representing the prevailing conditions on sub-humid regions of the tropics. Also, data for one short term trial at Kenya Agricultural and Livestock Research Organization (KALRO) Kakamega station is included.